TI_GERICHTE 12.2012.79 vom 7. November 2013 , Banca - obbligo di informazione - responsabilità - conto in rosso - rispetto dei margini - TI Tribunale d'appello (2013)
Banca - obbligo di informazione - responsabilità - conto in rosso - rispetto dei margini